Sustainable, Inclusive Agriculture Sector Growth in Armenia : Lessons from Recent Experience of Growth and Contraction - Christensen, Garry (World Bank, Washington, DC, 2018)
This Systematic Country Diagnostic (SCD) for Armenia has been prepared with the aim to identify key challenges and opportunities to advance the twin goals of ending absolute poverty and boosting shared prosperity. The review of Armenia’s agriculture sector forms part of this background material. Following an overview of the sector’s major characteristics, the study analyses the determinants of agriculture sector growth from 2004-2015, a period characterized by both expansion and contraction. The links between this growth and employment creation are then considered, followed by review of the inclusiveness of observed sector growth. Agriculture sector resilience to exogenous shocks is also examined, at both sector and household level. The study concludes by assessing the implications of the analysis for the four original hypotheses